Altered transcallosal fiber count and volume in high-functioning adults with autism spectrum disorder. (June 2022) - Nickel, Kathrin; Perlov, Evgeniy; Reisert, Marco; Runge, Kimon; Friedel, Evelyn; Denzel, Dominik; Ebert, Dieter; Endres, Dominique; Domschke, Katharina; Tebartz van Elst, Ludger; Maier, Simon
Abstract: An altered pattern of information processing has been hypothesized in autism spectrum disorder (ASD), characterized by enhanced local network connectivity and reduced long-distance communication. Previous findings of impaired white matter integrity in the genu and the body of the corpus callosum already indicated reduced long-distance connectivity in patients with ASD. However, it remained unclear how this reduced white matter integrity affects the structural connectivity of the corresponding brain areas. To this end, we analyzed magnetic resonance images (MRI) from 30 participants with high-functioning ASD and 30 typically developed individuals using a global tracking approach to estimate the fiber count and volume of the transcallosal fiber tracts of the five corpus callosum subsections. A reduced fiber count and fiber volume in the anterior subsection of the corpus callosum was detected, supporting the hypothesis of reduced long-distance connectivity in ASD.